Expressive Function of Contrastive Lexico-Stylistic Means in Publicistic Text (Proceedings of Southern Federal University. Philology, 2019)
Anna V. Romanova (Penza, Russian Federation)The article describes the methods of organizing reportage prose based on the principle of contrast. On the example of the analysis of the journalistic text devoted to the topic of the dying of Russian villages, the lexical and stylistic means that contribute to the organization of the entire material as a whole are considered, and their functions at the context level are described, and conclusions are made.Key words: lexico-stylistic means, contrast, opposition, symbol, psychological landscape.DOI 10.23683/1995-0640-2019-3-124-129